2010
DOI: 10.1308/003588410x12628812459850
|View full text |Cite
|
Sign up to set email alerts
|

Staged carotid endarterectomy under local anaesthetic in patients requiring cardiac surgery

Abstract: This study demonstrates that a policy of selective screening for significant carotid artery disease in cardiac surgical patients combined with a strategy of CEA under local anaesthesia prior to unselected cardiac surgery (CABG with or without valve surgery) leads to rates of peri-operative CVA, myocardial infarction and death comparable to rates published for CEA prior to isolated CABG surgery. Furthermore, it reduces the risk of peri-operative stroke and 30-day mortality to that observed in patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…Stroke risk has been shown to decrease more for patients staged to CEA before CABG than those staged to CABG before CEA [9]. Staged procedures reduce the stroke risk of CABG patients with carotid disease to that of CABG patients without carotid disease [10]. Nevertheless, completing carotid surgery several days to weeks before CABG leaves the patient at risk for postoperative MI, the highest incidence of perioperative MI occurring on postoperative day 3 [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke risk has been shown to decrease more for patients staged to CEA before CABG than those staged to CABG before CEA [9]. Staged procedures reduce the stroke risk of CABG patients with carotid disease to that of CABG patients without carotid disease [10]. Nevertheless, completing carotid surgery several days to weeks before CABG leaves the patient at risk for postoperative MI, the highest incidence of perioperative MI occurring on postoperative day 3 [11].…”
mentioning
confidence: 99%
“…Nevertheless, completing carotid surgery several days to weeks before CABG leaves the patient at risk for postoperative MI, the highest incidence of perioperative MI occurring on postoperative day 3 [11]. Many studies reporting staged results do not report the length of time between operations, while those that do range from 2 to 32 days [5,10,[12][13][14][15]. One study compared early and late outcomes with 3 approaches (synchronous CEA and open heart surgery, staged CEA and open heart surgery and staged carotid artery stenting and open heart surgery), including interstage events as a risk factor for outcomes after open heart surgery [16].…”
mentioning
confidence: 99%
“…There were no lethal outcomes, cerebral circulation disorder in the postoperative period was revealed in 1 patient (6.7%) (24). Several studies analyzed outcomes of different timing of interventions in patients with combined pathologies (25,26). In 2010, Kar et al (25) published the results of aortic stenosis treatment (AV area <1.0 cm²) among patients with carotid artery stenosis in Cleveland Clinic, USA from 1998 to 2005.…”
Section: Surgery Of Vhd and Carotid Artery Diseasementioning
confidence: 99%
“…At the same time, in the group of patients in whom only AVR was performed, there were no lethal cases or acute disturbance of cerebral circulation during the 1-year of follow-up. Birchley et al (26) presented the results of treatment of patients with carotid disease and VHD: 100 patients underwent CE before open-heart surgery (in a screening study of 11394 patients, critical carotid stenosis was revealed in 100 -0.87%); then, CABG was performed in 80 patients, the rest underwent CABG in combination with VHD surgery. Stroke developed in 1% of patients after carotid endarterectomy and before CABG, and in2% after CABG.…”
Section: Surgery Of Vhd and Carotid Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation